An Analytical Study of the Pattern of Teaching Insight Meditation of the Most Venerable Paṇḍitārāma Shwe Taung Gon Sayādaw U Paṇḍitābhivaṁsa - Sudassanā, Nun; Mahathanadull, Sanu (The Journal of International Association of Buddhist Universities (JIABU), 2019)
The aims of this paper are: 1) to analyze of the pattern of Insight Meditation in Theravāda Buddhism, 2) to study the life and the works of the Most Ven Paṇḍitārāma Shwe Taung Gon Sayādaw, 3) to study of the Pattern of teaching Insight Meditation of the Most Ven Paṇḍitārāma Shwe Taung Gon Sayādaw. This research methodology based on the life and work of the Most Venerable Paṇḍitārāma Shwe Taung Gon Sayādaw. Needless to say, the Most Ven. Paṇḍitārāma Shwe Taung Gon Sayādaw established many meditation centers around the world, and he had a great skill to teach Vipassana meditation. So that the number of Buddhist practitioner from the West as well as the East follow his footsteps on the Dhamma. Meticulous research from this study finds an instruction of Meditation Methods to Meditator, the rules of Meditation Center and Disciples of the Most Sayādaw.